Reduced deactivation of mechanochemically delaminated hierarchical zeolite MCM-22 catalysts during 4-propylphenol cracking - Silva, Laura L. [UNESP]; Stellato, Michael J.; Rodrigues, Mariana V. [UNESP]; Hare, Bryan J.; Kenvin, Jeffrey C.; Bommarius, Andreas S.; Martins, Leandro [UNESP]; Sievers, Carsten (Elsevier, 2022)
The delamination of MCM-22 using shear forces in a vibratory ball mill, rather than chemical surfactants and sonication, is illustrated. The resulting material has comparable or improved physical properties compared to chemically delaminated MCM-22 without a significant loss of acid sites. The mechanical treatment affected the initial rate of 4-propylphenol cracking to phenol and propylene, a model reaction for lignin-derived aromatics, much less than chemical delamination. It also shows improved deactivation resistance for this reaction known to experience fast deactivation by pore blockage.
Keywords: Catalysis; Deactivation; Hierarchical zeolites; Mechanochemistry; Synthesis